2014
DOI: 10.5489/cuaj.1514
|View full text |Cite
|
Sign up to set email alerts
|

Tumour stage on re-staging transurethral resection predicts recurrence and progression-free survival of patients with high-risk non-muscle invasive bladder cancer

Abstract: Introduction: To identify patients who should be considered for early radical cystectomy, we evaluated the clinical and pathological variables affecting the outcome of patients with high-risk nonmuscle invasive bladder cancer (NMIBC) who underwent re-staging transurethral resection (re-TUR). Methods: We reviewed the clinical data of 453 patients treated for urothelial carcinoma between 2006 and 2010. In total, 94 patients underwent re-TUR after their initial TUR. Of these, 72 were not upstaged to muscle invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…Despite proven reTURB benefits, its timing is not well established. Available literature reveals a wide variation of time oscillating from an immediate to 12 weeks after the primary TURB [7,8]. Recently, Baltaci et al [15] analyzed the effect of the reTURB timing on treatment results, showing that the interval between first and second TURB should be ≤42 days in order to attain lower recurrence and progression rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite proven reTURB benefits, its timing is not well established. Available literature reveals a wide variation of time oscillating from an immediate to 12 weeks after the primary TURB [7,8]. Recently, Baltaci et al [15] analyzed the effect of the reTURB timing on treatment results, showing that the interval between first and second TURB should be ≤42 days in order to attain lower recurrence and progression rates.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical guidelines by the European Association of Urology and the American Urological Association recommend reTURB to be performed within 2-6 weeks after primary TURB. However, these recommendations are based on low levels of evidence [7][8][9][10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies already reported higher recurrence (45% [29] to 84% [30]) and progression rates (16% [27] to 76% -includes …”
Section: Discussionmentioning
confidence: 99%
“…Approximately, 75% of the BUC patients present non-muscle-invasive bladder cancer (NMIBC; stage Ta-1). Surgical removal by TUR of bladder tumor is still the major treatment of NMIBC; yet, half of NMIBC patients treated with TUR have a recurrence of the disease and 5-25% progressed to muscle-invasive bladder cancer (MIBC, stage T2 and above) after repeated recurrences (4). Patients with MIBC are at high risk of local invasion and distant metastasis, despite radical cystectomy and pelvic lymph-node dissection, up to 50% of patients still develop tumours at distant sites and exhibit a less favorable prognosis with a 5-year survival of <50% (5,6).…”
Section: Introductionmentioning
confidence: 99%